Chk1 inhibition significantly potentiates activity of nucleoside analogs in TP53-mutated B-lymphoid cells - Zemanova, Jana; Hylse, Ondrej; Collakova, Jana; Vesely, Pavel; Oltova, Alexandra; Borsky, Marek; Zaprazna, Kristina; Kasparkova, Marie; Janovska, Pavlina; Verner, Jan; Kohoutek, Jiri; Dzimkova, Marta; et al. (Oncotarget, 2016)
Treatment options for TP53-mutated lymphoid tumors are very limited. In experimental models, TP53-mutated lymphomas were sensitive to direct inhibition of checkpoint kinase 1 (Chk1), a pivotal regulator of replication. We initially tested the potential of the highly specific Chk1 inhibitor SCH900776 to synergize with nucleoside analogs (NAs) fludarabine, cytarabine and gemcitabine in cell lines derived from B-cell malignancies. In p53-proficient NALM-6 cells, SCH900776 added to NAs enhanced signaling towards Chk1 (pSer317/pSer345), effectively blocked Chk1 activation (Ser296 autophosphorylation), increased replication stress (p53 and γ-H2AX accumulation) and temporarily potentiated apoptosis. In p53-defective MEC-1 cell line representing adverse chronic lymphocytic leukemia (CLL), Chk1 inhibition together with NAs led to enhanced and sustained replication stress and significantly potentiated apoptosis. Altogether, among 17 tested cell lines SCH900776 sensitized four of them to all three NAs. Focusing further on MEC-1 and co-treatment of SCH900776 with fludarabine, we disclosed chromosome pulverization in cells undergoing aberrant mitoses. SCH900776 also increased the effect of fludarabine in a proportion of primary CLL samples treated with pro-proliferative stimuli, including those with TP53 disruption. Finally, we observed a fludarabine potentiation by SCH900776 in a T-cell leukemia 1 (TCL1)-driven mouse model of CLL. Collectively, we have substantiated the significant potential of Chk1 inhibition in B-lymphoid cells.
Keywords: Mitosis; apoptóza; Mice, Transgenic; lidé; gemcitabin; Nucleosides; myši transgenní; Cell Proliferation; mitóza; Apoptosis; Deoxycytidine; Cell Line, Tumor; screeningové testy protinádorových léčiv; B-lymfocyty; Vidarabine; Pyrazoles; Mutation; Signal Transduction; Cell Survival; buněčný cyklus; nukleosidy; TP53; vidarabin; Cell Cycle; myši; pyrimidiny; Humans; nucleoside analogs; Mice; mutace; chronic lymphocytic leukemia; proliferace buněk; signální transdukce; viabilita buněk; checkpoint kinase 1/Chk1; pyrazoly; zvířata; SCH900776; checkpoint kinasa 1; Checkpoint Kinase 1; B-Lymphocytes; Tumor Suppressor Protein p53; Animals; nádorový supresorový protein p53; nádorové buněčné linie; chronická lymfatická leukemie; Cytarabine; Gemcitabine; Drug Screening Assays, Antitumor; Pyrimidines; cytarabin; deoxycytidin; Leukemia, Lymphocytic, Chronic, B-Cell